(untitled) (Agricultural Engineering, 2020)
The work presents a complex analysis and cost accounting of beet sugar cultivation in 2018/2019 campaign for individual farms of Lublin region. The economic results obtained by producers are mainly affected by indirect costs accounting for 60.11% of the revenue from the total production. Within this group of costs, the major components are sowing service, harvest and soil liming operations reaching 39.38%. Sugar beet production in the analyzed campaign was profitable, with the profitability index of 1.24 and unit production cost 14.33 PLN∙dt−1 is considered one of the profit-making activities in agricultural production, yet it is characterized by a high production cost that gobbled up to 80.39% of the total revenue in the analyzed 2018/19 campaign. The main factor influencing the income from sugar beet cultivation was the price for the raw material, which in the considered business year in relation to the previous season increased by only 0.77 PLN∙t−1.